Identifying a common data model approach for veterinary medical records - Holbrook, Ellen, author; Strecker, Joseph, author; VandeWoude, Susan, author (Colorado State University. Libraries, 2017)
Observational Medical Outcomes Partnership (OMOP) and Systematized Nomenclature of Medicine (SNOMED) are common clinical terminologies used to encode human electronic medical records and allow for modeling of diseases and other factors of interest. However, veterinary medical records have vastly lacked this level of organization. In partnership with UC Denver's Anschutz Medical Campus and other institutions with a similar medical-veterinary school partnership, this project aims to determine a database structure to align veterinary records with OMOP's Common Data Model and enhance One Health and translational medicine concepts by establishing encoding and modeling procedures applicable to both human and veterinary medicine.
139 - Elle Elnes Holbrook